The observational method in civil engineering : minimising risk, maximising value - Powderham, Alan J.; O'Brien, Anthony (Abingdon, Oxon ; Boca Raton, FL : CRC Press, Taylor & Francis Group, 2021)
"Twelve case histories from major civil engineering construction projects show how the Observational Method improves communication and collaboration, thereby cutting costs and time, increases safety, and enhances collaboration between design and construction teams"--
OCLC-licensed vendor bibliographic record.
Keywords: Civil engineering -- Case studies; Construction industry -- Management -- Case studies; Observation (Scientific method) -- Case studies